The Preservation and Dissemination Strategy of Toba Batak Indigenous Knowledge for Millennial Generations - Afryna Veronica (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
The present era is an era where everyone cannot be separated from knowledge. Indigenous Knowledge (IK) is one of the undocumented knowledge. This study analyzes IK preservation and dissemination strategy for the millennial generation of the Batak Toba tribe who are living overseas. This research is focused on the preservation and dissemination of IK, namely the Batak Toba language and script. The method used in this study is a qualitative research method, where data collection obtained through observation, interviews, and document analysis. The result of the study is that in the preservation and dissemination of the Batak Toba language and script using the World Bank theory which consists of six steps, some obstacles are still encountered. This obstacle causes many of the Batak Toba tribe overseas to prefer not to share and disseminate the Batak Toba language and script for the current generation/millennials. It is very unfortunate because the Batak Toba language and script are a national identity.